Enhanced thermomechanical fatigue resistance in W10Re alloys: Microstructural and surface engineering approaches - Michael Sommerauer; Benjamin Seligmann; Hannah Gottlieb; Anton Hohenwarter; Jeong-Ha You; Neil Bostrom; Reinhard Pippan; Maximilian Siller; Verena Maier–Kiener (Nuclear Materials and Energy, 2024)
Thermomechanical fatigue of refractory metals is commonly observed in high-temperature environments like first walls and divertors for proposed fusion reactors or X-ray anodes for medical imaging. Typically, alloying with rhenium or optimized microstructures are employed to counteract or delay the detrimental effects of fatigue in tungsten. Additionally, a novel concept is the utilization of surface structures to compensate cyclic thermal stresses. This work aimed to investigate the combination of these approaches, by comparing two W10Re alloys with vastly different microstructures, as well as engineered surface conditions of varying scales. Samples were subjected to thermocyclic fatigue under pulsed electron beam exposure, mimicking the surface temperatures typically encountered in a rotating X-ray anode. Analysis of several in-situ data streams, post-mortem investigations by metallography, and finite element methods revealed the interplay between microstructure and surface modifications. The columnar microstructure exhibited higher resistance to severe surface damage compared to the globular one, linked to the deflection of cracks along grain boundaries and subsequent melting. Coarse structuring was found to partly relieve the surface stresses during thermal cycling, preventing most of the damage accumulation. A full damage relief and performance equivalence between columnar and globular microstructure was achieved by engineering fine-structured surfaces, which led to a ten-fold increase in fatigue resistance over the non-structured condition.